The Relationship Between Internal Employer Branding and Talent Retention: A Theoretical Investigation for the Development of a Conceptual Framework - Ahmed, Rizwan Raheem; Azam, Muhammad; Qureshi, Jawaid Ahmed; Hashem E, Alharthi Rami; Parmar, Vishnu; Md Salleh, Nor Zafar (Frontiers in Psychology, 2022)
The focus of this paper is to develop a comprehensive conceptual framework for the relationship between internal employer brand image and talent retention. An extensive and semi-systematic literature review identified a number of antecedents and consequences that have been empirically tested in various cutting-edge research studies that were conducted around the world. The existing literature is reviewed using a topical approach, and 66 research studies, most recent from various repositories, were carefully chosen and reviewed based on the criteria. Such studies have been discerned and synthesized in order to establish a complete and accurate understanding of the phenomenon. Finally, a comprehensive and relatively rich conceptual framework has been proposed for future empirical explanations in various social settings via prospective research.